FACTORS AFFECTING CONSUMERS IN BUYING A HOUSE AT GRIYA SRIMAHI INDAH BEKASI UTARA - Siahaan, Christine Yolanda; Sembiring, Carolina (Fundamental Management Journal, 2021)
This study aims to determine the effectqof price,qlocation andqbuilding on theqdecision toqbuy a house in Griya Srimahi Indah Housing, Bekasi Utara. The data source used is primary data obtained through distributing questionnaires to 75 respondents, while secondary data is obtained through literature studies from the housing sector by searching for data via the internet related to this research. The research method used in this research is quantitative analysis techniques. While the data analysis used SPSS 22, Classical Assumption Test, Multiple Linear Aggression and Hypothesis Test to test the data statistically. Throughqthis researchqit is knownqthat the questionnaire data isqdeclared valid because r count> r table, that is, each r count> 0.2272. Likewise, the questionnaire data was also declared reliable because Cronbach's alpha> 0.60, namely 0.941> 0.60. The conclusion of this study is that the price factor partially does not have a significant effect on the purchasing decisions of residents of Griya Srimahi Indah Housing. While the location and building partially have a significant effect on the purchasing decisions of residents of Griya Srimahi Indah Housing. The price, location and building factors simultaneously have a significant effect on the purchasing decisions of residents of Griya Srimahi Indah housing. The location variable is the variable that has the most dominant influence on the purchasing decisions of residents of Griya Srimahi Indah Housing. Theqcoefficient ofqdetermination (Adjusted RqSquare) is 0.922. This meansqthat 92.2% ofqpurchasing decisionsqcan be explainedqby price, location andqbuilding variables. Whileqthe remaining 7.8% isqexplained byqother factors or variablesqwhich are notqexamined inqthis thesis. The suggestion that the authors can give is that housing developers need to increase the application of prices in housing marketing, if you want to create purchase decisions and can generate profits for both the company and for residential consumers. Housing developers need to add several facilities that can provide added value to the residence, such as a children's playground, land to build a minimarket or do greening in the Griya Srimahi Indah housing area. It is necessary to study other factors that can influence purchasing decisions, because by knowing the many factors that can influence purchasing decisions, developers will be better able to carry out housing development in accordance with market demand. Keywords: price, location, building and buying decision.